Association Of Maternal Age And Hemoglobin Level With Apgar Score Of Newborns In A Tertiary Care Hospital Of Suburbs Of Islamabad - Muhammad Hassaan Farooq; Afnan Rizwan; Irfan Afzal Mughal; Syed Haider Raza Rizvi; Amna Faruqi; Asma Irfan (Journal of Rawalpindi Medical College)
Objectives: To determine the association of Apgar score with maternal age and hemoglobin.